Dynamic study of critical factors of explosion accident in laboratory based on FTA. (October 2020) - Zhu, Chengyuan; Tang, Sen; Li, Zili; Fang, Xiuting
Highlights: A general framework is proposed for fault tree in laboratory explosion accident. BDD is utilized for analysing qualitatively and quantitatively about the FT. A quantitative method of dynamic system changing with time is proposed. Critical BEs are identified considering the probability of the TE over the time. The results of different heuristic algorithms are used to filter priority algorithm. Abstract: Laboratory safety has been widely concerned, but fire, explosion, poisoning and other accidents occur from time to time. Among them, the proportion of safety accidents, casualties and economic losses caused by explosion are relatively high. In particular, the safety, reliability and maintainability of laboratories in colleges and universities and scientific research institutes should be evaluated and optimized. Therefore, it is necessary to use efficient, reliable and economical methods to identify and monitor the key factors that will cause explosion accidents in the laboratory. In this paper, through the combination of fault tree analysis (FTA) and binary decision diagram (BDD), the three main sources of explosion accidents in laboratory (gas cylinder, pressure device and hazardous chemicals) are analyzed quantitatively. When using BDD to simplify FT operation, a variety of event sorting methods are compared. Finally, it is found that "Level" and "AND" methods can provide a more convenient and reasonable number of cut sets. Considering different methods to measure the importance of basic events, it is found that similar results can be obtained. The importance of Critical is used to identify the importance of events, combined with its change with time, the change of importance is analyzed dynamically. The key factors from four aspects of "human", "machine", "environment" and "management" in laboratory explosion accident are determined. It provides a new idea for the dynamic safety management and maintenance of the laboratory, and puts forward some ideas for the new research content at the end of this paper.